ChemInform Abstract: A Combined Metal‐Halide/Metal Flux Synthetic Route Towards Type‐I Clathrates: Crystal Structures and Thermoelectric Properties of A8Al8Si38 (A: K, Rb, and Cs). Issue 10 (March 2015) - Baran, Volodymyr; Senyshyn, Anatoliy; Karttunen, Antti J.; Fischer, Andreas; Scherer, Wolfgang; Raudaschl‐Sieber, Gabriele; Faessler, Thomas F.
Abstract Single‐phase samples of K8Al8Si38 (I), Rb8Al8Si38 (II), and Cs7.9Al7.9Si38.1 (III) clathrates are obtained by flux melting of Al/Si powder with an excess of Al and the respective alkali halide salt as the flux (alumina crucible in Nb ampoules, 1173 K, 1 h).